Renal Protective Effect of N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) in Dahl Salt-Sensitive rats - Worou, Morel E. (Hypertension, 2015)
N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a natural tetrapeptide with anti-inflammatory and anti-fibrotic properties. Its effect on salt-sensitive (SS) hypertension is unknown. We hypothesized that in Dahl SS rats on high salt diet, Ac-SDKP prevents loss of nephrin expression and renal immune cell infiltration, leading to a decrease in albuminuria, renal inflammation, fibrosis and glomerulosclerosis. To test this, Dahl SS rats and consomic SS13BN controls were fed either a low salt (LS=0.23%NaCl) or high salt (HS=4%NaCl) diet and treated for 6 weeks with vehicle (veh) or Ac-SDKP at either low or high dose (800 or 1600 µg/kg/day, respectively). High salt increased systolic blood pressure in SS rats (HS+veh 186±5 vs. LS+veh 141±3 mmHg; p<0.005) but not in SS13BN rats. Ac-SDKP did not affect blood pressure. Compared to low salt, high salt induced albuminuria, renal inflammation, fibrosis and glomerulosclerosis in both strains, but the damages were higher in SS compared to SS13BN. Interestingly, in SS13BN rats, Ac-SDKP prevented albuminuria induced by high salt (HS+veh 44±8 vs. HS+low Ac-SDKP 24±3 or HS+high Ac-SDKP 8±1 mg/24h; p<0.05); whereas in SS rats only high Ac-SDKP dose significantly attenuated albuminuria (HS+veh 94±10 vs. HS+high Ac-SDKP 57±7 mg/24h; p<0.05). In both strains, Ac-SDKP prevented high salt-induced inflammation, interstitial fibrosis and glomerulosclerosis. In summary, in SS rats on high salt diet, at low and high doses, Ac-SDKP prevented renal damage without affecting the blood pressure. Only the high dose of Ac-SDKP attenuated high salt-induced albuminuria. Conversely, in SS13BN rats, both doses of Ac-SDKP prevented high salt-induced renal damage and albuminuria.